Interventional Cardio-Oncology: Adding a New Dimension to the Cardio-Oncology Field - Liu, Victor Y.; Agha, Ali M.; Lopez-Mattei, Juan; Palaskas, Nicolas; Kim, Peter; Thompson, Kara; Mouhayar, Elie; Marmagkiolis, Konstantinos; Hassan, Saamir A.; Karimzad, Kaveh; Iliescu, Cezar A. (Frontiers in Cardiovascular Medicine, 2018)
The management of cardiovascular disease in patients with active cancer presents a unique challenge in interventional cardiology. Cancer patients often suffer from significant comorbidities such as thrombocytopenia and coagulopathic and/or hypercoagulable states, which complicates invasive evaluation and can specifically be associated with an increased risk for vascular access complications. Furthermore, anticancer therapies cause injury to the vascular endothelium as well as the myocardium. Meanwhile, improvements in diagnosis and treatment of various cancers have contributed to an increase in overall survival rates in cancer patients. Proper management of this patient population is unclear, as cancer patients are largely excluded from randomized clinical trials on percutaneous coronary intervention (PCI) and national PCI registries. In this review, we will discuss the role of different safety measures that can be applied prior to and during these invasive cardiovascular procedures as well as the role of intravascular imaging techniques in managing these high risk patients.